Μετρήσεις ηλιοφάνειας στην Κύπρο - Μικαίος, Ιωσήφ (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
The production of electricity through photovoltaic and other systems is being promoted in recent years both in Cyprus and worldwide. However, the power generation from these systems is based on three key factors, first the location of the installation, second in hour / day / month and third in weather conditions. The only unpredictable parameter that can not be computed by models is the weather. This particular research studies the changes in solar radiation (global, diffuse and direct radiation) when the clouds reach near the solar disk as well the enhancements of global radiation that can occur during the passage of the cloud. These data are received in Cyprus (latitude 34.7 inches, length 32.6 ° E). More specifically, the study of the movement of crowds in the spring of 2018 in March and April for 3 different occasions and also the phenomenon of enhanced global radiation on March 30, 2018, was observed. The aid observed has exceeded 1100 W/m2 which corresponds to 115% of the theoretical value calculated by the Bird and Hulstrom computational model for the specific cases. We also took measurements for another 3 days where global radiation values were higher than the expected value for those hours when compared to a day when there were no clouds. On April 9th, an increase in global radiation was observed at 11:00 at 1,000 W/m2; on 11th of April, in many cases between 11:00 and 12:00, values exceeding 1,000 W / m2 were observed, and on April 28th at 8:30 am in the morning there was an increase in global radiation at 750 W/m2 in contrast to 650 W/m2 which is the normal value for this time. These long periods of high radiation, along with the fall in temperature due to the presence of clouds, can increase the efficiency of photovoltaic modules and cause irreparable damage to photovoltaic inverters.
Keywords: Sun; Radiation; Weather; Clouds; Ήλιος; Ακτινοβολία; Καιρικές συνθήκες; Σύννεφα